Legal Protection of Consumers in Electronic Transactions in the Digital Era. - Nurhayati, Rika (Ilomata International Journal of Social Science, 2024)
This study aims to analyze legal protection for consumers in electronic transactions in Indonesia, focusing on the challenges faced by consumers and the effectiveness of existing regulations. The research issues include consumers' lack of understanding of their rights, dissatisfaction with dispute resolution mechanisms, and the high rate of online fraud. The methodology used is a qualitative approach with normative juridical studies, where data was collected through in-depth interviews with 50 respondents consisting of consumers, business actors, and legal experts. Additionally, documentation studies and direct observations were conducted to further explore consumer protection practices. The research results show that 76% of respondents feel they lack understanding of their rights as consumers, while 82% reported experiencing online fraud. Dissatisfaction with dispute resolution mechanisms reached 68%. These findings indicate the need for increased consumer education and improvements in dispute resolution mechanisms to make them more efficient. This study concludes that although consumer protection regulations exist, their implementation is still far from ideal. Therefore, it is recommended that the government and business actors collaborate to raise public awareness about consumer rights and strengthen regulations and transparency in electronic transactions.